Education in Religious Freedom - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2016)
The author emphasizes the crucial relevance of religious liberty and freedom of expression for a harmonious and peaceful development of modern societies. He follows the prophetic Declaration of Religious Freedom of Second Vatican Council (1965) with its constitutional limitation of governmental powers in matters of religion. The high value of religious freedom is judged as bulwark of all human rights and true capstone of sound human and societal developments, which have to be guarded against any form of infringements. In this regard, a reasonable education in religious freedom and liberty is indispensable for young people of the twenty-first century. Education in religious freedom in the context of moral and religious formation is based on the dignity of every human person and promotes a deeper mutual and cultural understanding by respecting the conscience of every human person. It thus carries the potential to diminish conflicts and clashes in a sustainable way. Educational reforms in countries have to include the high value of religious liberty and freedom as a main element and condition for human dignity and a peaceful global development.

Science and Laudato Si’ on the Paradigm Shift towards Sustainable Development - Gassner, Franz (The Journal of the Macau Ricci Institute, 2018)
For sustainability researchers and global policy makers it is lucid clear that a radical turnaround of modern societies is needed to approach sustainable development paths. Pope Francis takes his stand on a basic paradigm shift in his Encyclical Letter Laudato Si’: Care for our Common Home (2015). He calls for a radical shift of mindsets and ecological and cultural conversion which are needed for sustainability and a life in dignity for all. The author compares aspects from sustainability research and Laudato Si’ and shows how science and Francis spiritual-theological take converge. Both call for the need of new mindsets and spiritual resources to nourish just life-styles and sustainable societies.

Ethical Investment’s Visible Hand: Methods And Transformative Potentials - Gassner, Franz (The Journal of the Macau Ricci Institute, 2021)

Education in Religious Freedom: Path to Peace and Stability - Gassner, Franz (Orientis Aura, 2016)

Learning God’s Mercy: Spiritual Transformation According to Hos 11:8 - Gassner, Franz (The Journal of the Macau Ricci Institute, 2022)
A growing focus on God’s mercy and forgiveness emerged in the wake of the recent Pontificates of John Paul II, Benedict XVI, and Francis. Our time with its multiple crises cries for healing, forgiveness, and the experience of God’s mercy. In social, political, and global terms, humanity craves for “lasting peace, born of the marriage of justice and mercy” (John Paul II, 2001, no. 15). The experience of God’s forgiveness, merciful healing and new life has been expressed many times in the Bible. But, theologically, it has never been formulated as directly as in Hosea 11:8, when God’s own heart becomes “turned over”, “converted” following the blaze of his own overwhelming compassion, paving the way for a fundamental spiritual transformation, rooted in forgiveness and mercy, that opens wellsprings of dignity, healing, and new life for all.

From Maximum Illud 1919 to the First National Synod Primum Concilium Sinensis 1924 in Shanghai: Historical & Theological Perspectives - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2022)
Section: Articles

“To Listen to the Language of Nature and to Act Accordingly” :: Natural Law as Beacon guiding to Human Flourishing and Ecological Civilization - Gassner, Franz (Orientis Aura: Macau Perspectives in Religious Studies, 2021)
The article sets off from a speech given by Benedict XVI in the German Bundestag in 2011, where he requested an ecological learning process to aim at sustainable human development. Appreciating the Ecological Movement, he asked to learn to listen to Nature’s language and act accordingly, which he applies analogically to “human ecology”. The article bridges elements of “Listening to Nature” and the Natural Moral Law Tradition in Benedict’s speech and in Francis’ Encyclical Letter Laudatu Si’ inview of serving human flourishing in an ecological civilization. Keywords: Natural Moral Law; Nature, Laudatu Si’, Benedict XVI, Francis; Ecological Civilization/生態文明, Sustainable Development, Ecology of Man.
Number: 6

Korean memorial service for the dead: a re-evaluation of the Christians' understanding - Song, Jeongmin (University of Saint Joseph, 2016)
Keywords: Thesis and Dissertations Master of Religious Studies (MRS); University of Saint Joseph

The role of spirituality and religion in counseling and pyschotherapy of christian clients - Tse, Chau Hung (University of Saint Joseph, 2018)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Study of everyday moral reasoning of senior secondary students in Macao - Ng, Sio Lin (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

Green Space in Macau: Comparative Analyses and Suggestions for New Reclamation Areas - Xiao, Yuan Bin (University of Saint Joseph, 2020)
Keywords: Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Strategies to reduce greenhouse gas in Macau: assessment on the potentials of natural gas development - Lei, Chon Kio (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Traffic Pollution & Urban Design, Alternatives for Developing Healthy Historical Centers: The Case of Macao - Pinheiro, Francisco Vizeu (University of Saint Joseph, 2017)
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

A Study on Spiritual Well-Being of Secondary School Teachers in Macau - Wong, Kuan Cheng (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

A Psychological and Phenomenological Analysis of Chinese People Who Are Not-Capable-Of-Saying-No - Song, Sok Fong (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Philosophy (MPH); University of Saint Joseph

Environmental Education in Macau’s Schools: A Case Study on Teachers' Perceptions of Experiential Pedagogies - Reh, Paul Thu (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

A Historical Invertigation into the Pentecostal and Charismatic Movement in Macau's Protestant Churches: From Thomas J. Mcintosh to the Present Day - Ho, Kei Tsui (University of Saint Joseph, 2022)
This dissertation is a comprehensive academic examination of the characteristics and complex historical progress within the Pentecostal and Charismatic Movement in Macau Protestant Churches. Since Macau hosted the first Pentecostal and Charismatic missionary, Thomas J. McIntosh, who entered China in 1907, the history of the Pentecostal and Charismatic Movement in Macau lacks a consistent and synthesized research until now. Thus, primary and secondary resources have been analyzed and reconstructed and historically interpreted to gain a better and deeper understanding of the emergence and development of the Pentecostal and Charismatic Movement within Macau’s Protestant Churches from the beginning up to the present day. This academic review makes an important contribution to Macau with respect to its historical development and will fill the gap in knowledge within the Global church history of the Pentecostal and Charismatic Movement. Key Words: Charismatic, Christianity in China, History of Missionaries in China, Macao, Macau, Pentecostalism, Protestant, T. J. McIntosh
Keywords: Thesis and Dissertations PhD in Religious Studies (D-RS); University of Saint Joseph

The relevance of philosophy, spirituality and religion in counselling & psychotherapy within Asia - kazmi, Sayed Shajaat Hussain (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Couselling and Psychotherapy (MCP); University of Saint Joseph

COP21 COMPLIANCE AND SUSTAINABLE DEVELOPMENT THROUGH INTEGRATED SOLID WASTE MANAGEMENT: IMPLEMENTATION PERSPECTIVES OF THE CIRCULAR ECONOMY IN THE PEARL RIVER DELTA AREA - Li, Warren Man Ho (University of Saint Joseph, 2022)
The global living standard improved significantly in the last decades and China moved 800 million people out of poverty since 1980. However, production and consumption in their current forms are unsustainable in matters of resource and energy use and involved emissions with their significant ecological impact. The global human community committed itself in the COP21 Agreement of Paris 2015 to reduce Green House Gas (GHG) emissions based on National Determined Contributions (NDCs) in order to limit the increase of global average temperature below 2°C or better 1.5°C above pre industrial levels. This commitment entails a comprehensive transformation of the current social and economic system in view of decoupling economic growth from both resource extraction and GHG emissions, in view of fostering a resource sensitive and CO2 neutral Circular Economy (CE) based on Sustainable Development (SD). China submitted its first Intended Nationally Determined Contributions (INDCs) in 2015 with policies and measures affecting 15 major areas. In 2020, President Xi Jinping announced the commitment to peak China’s carbon dioxide emissions before 2030 and achieving carbon neutrality before 2060. Proper and Integrated Resource and Waste Management is central on the way to achieve the transformation into a CE. The State Council of the People’s Republic of China (PRC) released its plan “生活垃圾分类制度实施方案” to promote source separation of household waste on March 30, 2017 aiming at the recycling rate for household waste to reach 35% by 2020 for the selected cities. The first China’s Mandatory Waste Source Separation Law “廣州 市生活垃圾分類管理條例” was enforced by the city of Guangzhou on July 1st, 2018. One of the key strategic plans in China is the development of the Greater Bay Area (GBA) with its comprehensive development plan released on February 18, 2019. Following the INDCs by China, parts of the GBA Development Plan emphasize that the development of the CE systems and the implementation of extended producer responsibility (EPR), are effective principles to provide financial incentives in view of reducing embedded emissions in material and processes. The present research studied, analysed, and compared the MSW treatment strategies, rules, regulations, and retrievable data, which lead to MSW source separation and the reverse logistic of separated waste among 4 selected cities Guangzhou, Zhuhai, and the 2 S.A.R.s of Hong Kong and Macao. The experience and comparison from Guangzhou and Hong Kong revealed that a Top-down approach in environmental policy decision making is more efficient and is able to implement necessary policies faster. However, the experiences from Guangzhou and Zhuhai indicate, that also a more participatory implementation process is crucial, as it enables the involved stakeholders to express their experiences and opinions properly, which can lead to a higher level of policy feasibility and acceptance and a smoother operation accompanied with a higher effectiveness. For the two SARs, to achieve the objective to increase the recycling rate, the local Government must seek approval from China’s Central Government to allow locally generated recyclable material, in their original form, to enter mainland China for further treatment and to be turned into secondary raw material. Without such a proper support by a reverse resource logistic from the mainland, the CE schemes, such as the Mandatory Waste Source Separation, Producer Responsibility Scheme (PRS), Waste Charging Scheme, are not able to be implemented effectively. The current approach of the Local Government purchasing of recycling and exportation services of recyclable materials from private companies, and the sole reliance on existing market forces to handle, process, and export recyclable material out of the S.A.R.s cannot ensure a reliable and continuous operation in view of mitigating involved emissions. By way of a comparative analyses, the present investigation works out and distils suggestions for best practices of implementing the CE to comply with targets of emission reductions
Keywords: Circular Economy (CE); Sustainable Development Goals (SDGs); Thesis and Dissertations PhD in Science (D-SC); University of Saint Joseph; Waste Hierarchy; Zeroand- Low-Waste-Systems

Senior secondary students perceptions of virtue and values: a case study in education in Macau - The Reh, Lawrence (University of Saint Joseph, 2019)
Keywords: Thesis and Dissertations Master of Education (MED); University of Saint Joseph

Food Waste Management In Macau: Assessing Public Awareness, Recycling Facilities, And Policy Implementations In Comparative Perspective - Hoi, Hang Ian (University of Saint Joseph, 2023)
Food waste has become an increasingly pressing issue worldwide, and Macau is no exception. A substantial portion of municipal solid waste in Macau is comprised of organic waste, with household food waste being a significant contributor. This can be attributed to households purchasing excessive food, preparing more than necessary, or not consuming items before they spoil, leading to detrimental resource and environmental impacts, particularly in the form of greenhouse gas emissions. It is crucial for Macau to develop a sustainable food waste management system that fosters prevention and responsible consumption and to develop food waste recycling habits among its residents. This study employed a two-pronged approach: a literature review of food waste source separation policies and practices in four neighboring regions to identify adaptable good practice examples for Macau, and a questionnaire survey completed by 143 local residents. The survey aimed to comprehend residents' behaviors and awareness regarding food waste prevention and treatment, evaluate their satisfaction with Macau's existing food waste recycling program, examine their resistance and motivation toward participating in the recycling program, and assess their attitudes toward implementing a polluter-pays-principle system in Macau. The survey aimed to provide insights into the current state of household food waste in Macau and inform future waste management policies and strategies of stakeholders. The survey findings highlight the need for enhanced public awareness and education on food waste prevention. Additionally, upgrading recycling facilities may encourage residents to participate more actively in food waste recycling. Ultimately, implementing suitable policies can help prevent food loss and waste and regulate food waste generation and elevate recycling rates. This study offers preliminary recommendations for policymakers or government entities as a orientation for future planning
Keywords: Food Loss and Waste (FLW); Food Waste Hierarchy; Food Waste Management; Food Waste Separation; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

INFORMAL RECYCLING IN MACAU: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - Ng, Sut Wa (University of Saint Joseph, 2023)
Informal recycling plays a crucial role in municiapl solid waste management in many cities, particularly in the global South. This study examines the practices, challenges, and opportunities of informal recycling in Macau, a small city and Self Autonomous Region (S.A.R.) in China. Using qualitative research methods, including semi-structured interviews, this study explores the motivations and strategies of informal recyclers, the challenges they face, and the potential for collaboration with formal waste management systems. The findings of this study reveal that informal recycling in Macau is a complex and multifaceted reality and practice that involves a range of actors, from waste pickers to small-scale processors to exporters, all with their specific challenges. Informal recyclers are motivated by economic necessity, and they employ a variety of strategies to collect and process recyclable materials. However, they also face significant challenges, including high rental and transportation costs, lack of manpower, China’s waste import policies and ensuing restrictions, fluctuating global price rates of materials and the unstable income as serious consequence, accompanied by limited support from the local Government. This study also identifies opportunities for sustainable development of informal recycling in Macau, supported by the analysis of data collected via questionnaire survey regarding Macau citizens’ waste separation habits and their willingness to pay for resource separation and recovering process. The identified oppurtunities include establishing partnerships between informal and formal waste management actors, improving the infrastructure, and introducing environmental levy system and consistent policies and regulations. Overall, this study contributes to a better understanding of the role of informal recycling sector in waste management in Macau and provides insights into potential strategies for improving the sustainability of resource and waste management practices in the city
Keywords: Circular Economy (CE); Informal Recycling; Integrated Solid Waste Management (ISWM); Recycline Rate; Sustainable Development Goals (SDGs); Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph; Waste Hierarchy

Adoption of Best Practices for Municipal Solid Waste Recycling Management in Macao - Li, Man Ho (University of Saint Joseph, 2017)
Municipal Solid Waste (MSW) is associated with industrialization, urbanization, and a modern economic development, covering several origins such as households and similar waste streams from commerce and trade. Inappropriate waste management impacts human health and the environment negatively, but also the economy and society in general. Waste is today also seen more and more as resource itself. The world trend is to move from mere waste management to a consistent form of resource management within a circular economy, e.g. in form of an Integrated Waste Management System (IMWS). Concerning Macao, MSW is being transported to the Macao Refuse Incineration Plant for thermal treatment with energy recovery. For 2014 and 2015, the amount of waste transferred to the Macao Refuse Incineration Plant for treatment shows a strong yearly increase (11.3 %) being expected to reach or even exceed the maximum allowable waste handling capacity in near future. Alternative methods for waste treatment and valorization are necessary for an effective and sustainable waste management system in Macao. In this research, three case-studies were carried out to analysis real case scenarios that are considered examples of well-functioning MSW management. They were: 1) LIPOR (Portugal); 2) Resinorte (Portugal) and 3) Hong Kong. A questionnaire was prepared and distributed to Macao residents in order to understand their perceptions and views on the existing solid waste recycling in Macao. According to the results of the case-studies and questionnaire, based on the “Polluter Pays Principle” and “Producer Responsibility Scheme”, the main objective of this research is to suggest best practices for waste recycling and management in Macao for the Government, Company, Recycling Trade Participator and the Individual Level
Keywords: Thesis and Dissertations Master of Environmental Sciences and Management (MESM); University of Saint Joseph

Abfaelle sind kostbar!" Konsumethische Perspektiven in Papst Franziskus' Enzyklika Laudaut Si - Gassner, Franz (Eine Wirtschaft, die Leben fördert wirtschafts- und unternehmensethische Reflexionen im Anschluss an Papst Franziskus, 2017)

Resources for Future in a Caring Economy - Gassner, Franz (Menschenrechte und Gerechtigkeit als bleibende Aufgaben, 2020)

Journalism Ethics and the Common Good: The Formation of Values and Virtues for Just and Harmonious Societies - Gassner, Franz; Simoes, José Manuel (Disentangled Vision On Higher Education: Preparing The Generation Next, 2022)